2015
DOI: 10.1038/nsmb.3090
|View full text |Cite
|
Sign up to set email alerts
|

miR-128 represses L1 retrotransposition by binding directly to L1 RNA

Abstract: VOLUME 22 NUMBER 10 OCTOBER 2015 nature structural & molecular biology a r t i c l e s microRNAs (miRs) are a class of small (~22-nt) genomically encoded molecules that inhibit translational initiation and stimulate decay of mRNA targets 1,2 . miRs are transcribed by RNA polymerase II and processed by the RNase III enzymes-Dicer and Drosha with its binding partner, DGCR8-to produce short double-stranded RNAs in the nucleus. One strand associates with the Argonaute (Ago) protein, thus forming the miR-mediated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(104 citation statements)
references
References 41 publications
8
95
0
Order By: Relevance
“…Nevertheless, our work, together with other studies performed in human cultured cells, indicates a role of DICER as a player in L1s regulation [77,82,83]. How DICER controls L1s still remains unclear and further investigations are needed.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Nevertheless, our work, together with other studies performed in human cultured cells, indicates a role of DICER as a player in L1s regulation [77,82,83]. How DICER controls L1s still remains unclear and further investigations are needed.…”
Section: Resultsmentioning
confidence: 65%
“…How DICER controls L1s still remains unclear and further investigations are needed. Recently, a study performed in human cells indicated that a particular microRNA, miR‐128, was involved in the direct regulation of L1s transcripts . Nevertheless, miR‐128 is not expressed in mESCs (data not shown) and therefore cannot explain the regulation of L1s by DICER.…”
Section: Resultsmentioning
confidence: 97%
“…The HUSH complex and MORC2 have also been shown to target evolutionarily young euchromatic LINE1 elements for silencing by deposition of H3K9me3 . Posttranscriptional silencing of LINE1 RNA is mediated via RNA interference by small RNAs, such as piRNAs and rasiRNAs . PIWI proteins use piRNAs to guide the cleavage of LINE1 RNA in germ cells.…”
Section: Mechanisms Of Control Of Line1 Expression and Mobilizationmentioning
confidence: 99%
“…We have recently established that miRs (miR-128) can repress the activity of key enzymes in our cells, such as reverse transcriptase (RT) encoded by transposable elements (long-interspaced element-1, LINE-1 or L1) [29]. With this in mind we turned our attention to the most famous RT in human cells -telomerase -an enzyme which plays a crucial role in cancer, stem cells and aging [7][8][9].…”
Section: Identification Of Mir-128 As a Regulator Of Telomerasementioning
confidence: 99%
“…Most studies have, however, found it to act as a tumor suppressor and downregulation has been documented in a long list of human malignancies, including glioma, prostate, head and neck, lung and colorectal cancer, where it has been shown to function as an inhibitor of cancer cell growth and metastasis [22,[24][25][26][27][28]. We recently demonstrated that miR-128 regulates another cellular reverse transcriptase, namely the Long-Interspaced Element-1 (LINE-1 or L1) by directly interacting with ORF2 L1 RNA, which encodes L1 RT [29]. Derepression of L1 elements have been demonstrated to function as driver mutations during tumor initiation, as well as during tumor progression [30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%